High definition 3D models of small legume seed: a close up application to support ancient plant genomics - M. Balestra; F. Fattorini; R. Angeloni; L. Nanni; A. Mancini; R. Papa; R. Pierdicca (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Legume seeds are essential for nutrition and play crucial roles in food security, climate change mitigation, biodiversity conservation, and sustainability. Among them, the common bean (Phaseolus vulgaris L.) is the most widely cultivated and vital to the food value chain. Originating in Mesoamerica and independently domesticated there and in the Andes about 8,000 years ago, common beans have adapted to diverse environments globally following the Columbian exchange. Ancient DNA (aDNA) sequencing offers insights into the bean’s adaptation and evolution, but traditional methods struggle with detailed 3D phenotypic analysis due to the beans’ small size and the destructive nature of aDNA extraction. Expensive high-detail optical instruments are not commonly available in genetic labs. This research proposes macro-photogrammetry as a low-cost technique for creating detailed 3D digital replicas of beans. By using samples from archaeological sites in northern Peru, this method preserves phenotypic information despite the destruction of physical samples during DNA extraction. The study details the process of capturing high-detail images with specialized equipment to build a digital phenotype library, preserving the morphological features of ancient beans for further study and future comparison with modern varieties.